Controlled ∗-Operator Frames on Hilbert C∗-Modules. (9th April 2021) - Labrigui, Hatim; Touri, Abdeslam; Rossafi, Mohamed; Kabbaj, Samir
Abstract : In this paper, we study the concept of controlled ∗ -operator frames for the space of all adjointable operators on a Hilbert C ∗ -module H. Also, we discuss characterizations of controlled ∗ -operator frames and we give some properties. Some illustrative examples are provided to advocate the usability of our results.